The impact of informal social networks on integration - a case study of migrant learners at Jules High School in central Johannesburg. - Hoehne, Dalia (My University, 2013)
In the absence of governmental programs which facilitate and support integration, this study looks at strategies that migrants, and in particular migrant children themselves, develop and the experience they have of the process of integration into the South African host society. Thereby, this study assesses the role that informal social networks play for migrant learners at inner-city schools in Johannesburg with regards to their integration into the school environment in particular and into the broader host society in general. Following a case study approach, I primarily focused on the school, namely Jules High School, as an environment where such networks exist since the school environment is considered as a place where social contacts and interactions with the host population necessarily occur that can be vital in support of integration. In order to explore the role of informal social networks for migrant learners, quantitative interviews with 98 Jules High School students (survey) were conducted, complemented by a focus group discussion as well as qualitative interviews with three key informants.
Keywords: Social integration--South Africa.; Children of migrant laborers--Education--South Africa.; Students--Social networks--South Africa.